Learners’ Collocation Use in Writing: Do Proficiency Levels Matter? - Lateh, Nor Hazwani Munirah; Shamsudin, Sarimah; Raof, Abdul Halim Abdul; Mahmud, Najihah; Mohamed, Amaal Fadhlini; Nasir, Nazatul Syima Mohd; Hanapi, Nurul Fatihah (Universitas Pendidikan Indonesia, 2021)
Knowledge of collocation is important in enabling learners to use a language fluently. When learners can demonstrate a good command of collocation use as they write, this results in greater fluency and proficiency. The present study is a case study that investigated the collocational knowledge of ESL learners across different proficiency levels. Specifically, the extent to which the learners produce lexical collocation in writing is examined in the study. To this end, a writing task (an essay) was administered to elicit the written output of the learners. The procedure involved a total of n=120 undergraduate ESL learners (limited, modest, and proficient learners) studying at a public university in Malaysia. The essays collected in the study were analysed and compared in terms of the lexical collocation frequencies and categories. The results first revealed that the higher proficient students wrote slightly higher lexical collocations than their counterparts. The second finding, however, indicated that there is no significant difference in the proportion of lexical collocation (.05) written by the students, regardless of their proficiency levels. Thirdly, the results demonstrated that students of higher proficiency levels were able to write their essays with slightly more lexical collocation categories in comparison to lower proficiency level learners. Nonetheless, the students did not tap into all six lexical collocation categories in their writing. The findings of the study provide insights into the lexical collocation knowledge of Malaysian ESL undergraduates across various proficiency levels.